Posted by
**Tammy Evert** on
.

solve by substitution

5x-2y = -5

y - 5x = 3

could someone take a min a show me how to do this problem by steps so i can do the rest of my problems

and wait a min so i may ask questions. I m failing my algebra class and desparately need help.

5x-2y = -5

y - 5x = 3

take the second equation and solve for y.

y= 5x+3

Now,put that in the first equation for y.

5x-2(5x+3)=-5

and solve.

Tammy, I think you need a real tutor twice a week. Discuss this with your mom today. Your teacher probably has a list of tutors. They are not inexpensive.